Implementasi Manajemen Keuangan Madrasah Dalam Rangka Meningkatkan Mutu Pendidikan Islam - Rifdah Auva Apriliana; Dwi Putri Miftahatun Rodiyah; Bunga Melati Sukma; Desta Restu Puspitasari; Eka Salma Dina; Anaas Tri Ridlo Dina Yuliana (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This article focuses on discussing the implementation of financial management in madrasas, management connotes everything related to administrative control or management. This article also discusses various education financing management which play an important role in achieving educational goals and improving the quality of education. One of them is by improving the quality of education by knowing the national education standards that apply in Indonesia. Effective financial management will guarantee the benefit of educational institutions, so madrasah financial management must be handled seriously and responsibly to avoid unwanted things and can improve the quality of Islamic education.